Multicultural Representation in Sopo Jarwo Cartoon Series for The Reinforcement of Global Diversity Awareness - Kurniawan, Andriyanto; Widayati, Mukti; Nurnaningsih, Nurnaningsih (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
This study addresses the gap in integrating multicultural education into primary school curricula by utilizing digital media, specifically the Sopo Jarwo animated series. While prior research highlights the significance of multicultural education in fostering inclusivity and global diversity awareness, few studies have explored the role of animated media in achieving these objectives. This research aims to analyze the multicultural values embedded in Sopo Jarwo and evaluate their potential to strengthen the Pancasila Student Profile in elementary schools. Employing a qualitative descriptive case study approach, the study examined the first ten episodes of the series using semiotic analysis and Miles and Huberman's interactive model. Data were collected through non-participatory observation, transcription of dialogues, and annotation of visual and contextual elements. The findings reveal that Sopo Jarwo portrays key multicultural values, including portrays tolerance as a conflict resolution mechanism, community cooperation, interethnic harmony and inclusivity, also cross-generational learning through relatable characters and engaging narratives. These values are aligned with Indonesia’s Pancasila principles and hold significant educational potential. This research contributes to the growing discourse on media-based education and offers practical implications for curriculum development. By showcasing the educational value of digital media, this study underscores its broader relevance in fostering global awareness and cultural harmony in increasingly diverse societies.